Chromatin condensation fluctuations rather than steady-state predict chromatin accessibility. Issue 12 (13th May 2019) - Audugé, Nicolas; Padilla-Parra, Sergi; Tramier, Marc; Borghi, Nicolas; Coppey-Moisan, Maïté
Abstract: Chromatin accessibility to protein factors is critical for genome activities. However, the dynamic properties of chromatin higher-order structures that regulate its accessibility are poorly understood. Here, we took advantage of the microenvironment sensitivity of the fluorescence lifetime of EGFP-H4 histone incorporated in chromatin to map in the nucleus of live cells the dynamics of chromatin condensation and its direct interaction with a tail acetylation recognition domain (the double bromodomain module of human TAFII 250, dBD). We reveal chromatin condensation fluctuations supported by mechanisms fundamentally distinct from that of condensation. Fluctuations are spontaneous, yet their amplitudes are affected by their sub-nuclear localization and by distinct and competing mechanisms dependent on histone acetylation, ATP and both. Moreover, we show that accessibility of acetylated histone H4 to dBD is not restricted by chromatin condensation nor predicted by acetylation, rather, it is predicted by chromatin condensation fluctuations.